Non-linear Control Law for Articulated Serial Manipulators: Simulation Augmented with Hardware Implementation - Ullah, Muhammad Imran; Ajwad, Syed Ali; Irfan, Muhammad; Iqbal, Jamshed (Elektronika ir Elektrotechnika, 2016)
The performance of a robotic arm includes accuracy, repeatability and reliability to accomplish a task. These parameters, in turn, are function of associated control law. Multi-Degree Of Freedom (DOF) robotic arms, because of their inherent highly non-linear dynamics, demand sophisticated control laws. Trivial control strategies fail to cope with disturbances and uncertainties that are common in today’s plants. This paper presents the design, simulation and physical implementation of a non-linear control technique Variable Structure Control (VSC) for a 6 DOF arm. Based on the derived dynamic model of the arm and designed control law, simulations have been conducted in MATLAB/Simulink. The controller parameters have been tuned for optimal response. Various desired trajectories characterize the tracking performance of the control law. The simulation results have been then validated by implementing the law on a custom-developed novel AUTonomous Articulated Robotic Educational Platform (AUTAREP). Coupling effects between various joints of the robot have also been investigated. Results of this research find potential in industrial control of robotic manipulators to perform complex tasks. DOI: http://dx.doi.org/10.5755/j01.eee.22.1.14094